Predictability of Nonremitting Depression After First 2 Weeks of Antidepressant Treatment: A VAST‐D Trial Report. Issue 2 (3rd October 2019) - Hicks, Paul B.; Sevilimedu, Varadan; Johnson, Gary R.; Tal, Ilanit; Chen, Peijun; Davis, Lori L.; Vertrees, Julia E.; Mohamed, Somaia; Zisook, Sidney
Abstract : Objective: In this secondary analysis of data from the Veterans Affairs Augmentation and Switching Treatments for Improving Depression Outcomes (VAST‐D) study, the authors sought to determine the effectiveness of early improvement (or lack thereof) for predicting remission from depression with antidepressant therapy. Methods: This study used data from the VAST‐D study, a multisite, randomized, single‐blind trial with parallel assignment to one of three medication interventions for 1, 522 veterans whose major depressive disorder was unresponsive to at least one course of antidepressant treatment meeting minimal standards for dosage and duration. The authors calculated the positive predictive value (PPV) and negative predictive value (NPV) of early improvement on remission, response, or greater than minimal improvement from depression for various degrees of improvement (10%–50%) on the Quick Inventory of Depressive Symptomatology–Clinician Rated (QIDS‐C) at 1, 2, 4, and 6 weeks. Results: The end of week 2 of treatment was identified as the best time to evaluate early improvement. The presence of a ≥20% drop from the baseline QIDS‐C score by the end of week 2 resulted in a PPV for remission of 38% and an NPV of 93% by week 12. Extending the observational window to week 6 minimally improved NPV (97%). This association did not differ across treatment groups. Conclusions: A lack of early improvement at the end of week 2 of antidepressant therapy can be used to inform clinical decisions on the likelihood of nonremission of depression during the subsequent 10 weeks, even when dosage optimization is incomplete.